The Cyclic AMP (cAMP)-cAMP Receptor Protein Signaling System Mediates Resistance of Vibrio cholerae O1 Strains to Multiple Environmental Bacteriophages - Zahid, M. Shamim Hasan (American Society for Microbiology (ASM), 2010)
Toxigenic Vibrio cholerae, the causative agent of the epidemic diarrheal disease cholera, interacts with diverse environmental bacteriophages. These interactions promote genetic diversity or cause selective enrichment of phage-resistant bacterial clones. To identify bacterial genes involved in mediating the phage-resistant phenotype, we screened a transposon insertion library of V. cholerae O1 El Tor biotype strain C6706 to identify mutants showing altered susceptibility to a panel of phages isolated from surface waters in Bangladesh. Mutants with insertion in cyaA or crp genes encoding adenylate cyclase or cyclic AMP (cAMP) receptor protein (CRP), respectively, were susceptible to a phage designated JSF9 to which the parent strain was completely resistant. Application of the cyaA mutant as an indicator strain in environmental phage monitoring enhanced phage detection, and we identified 3 additional phages to which the parent strain was resistant. Incorporation of the cyaA or crp mutations into other V. cholerae O1 strains caused similar alterations in their phage susceptibility patterns, and the susceptibility correlated with the ability of the bacteria to adsorb these phages. Our results suggest that cAMP-CRP-mediated downregulation of phage adsorption may contribute to a mechanism for the V. cholerae O1 strains to survive predation by multiple environmental phages. Furthermore, the cyaA or crp mutant strains may be used as suitable indicators in monitoring cholera phages in the water.